Early Town Planning Legislation in Nova Scotia: The Roles of Local Reformers and International Experts - Grant, Jill; Vissers, Leifka; Haney, James (Urban History Review / Revue d'histoire urbaine, 2012)
In 1912 Nova Scotia was the second province in Canada to adopt a town planning act. Just three years later, the province substantially revised its act under the guidance of Thomas Adams, town planning advisor for the Commission of Conservation. The article examines the context within which Nova Scotia adopted and then overhauled its early planning legislation. While Canadian planning history generally credits Adams with rewriting the legislation, the article documents the mechanisms through which key local actors drove provincial policy. Changes to provincial legislation in Nova Scotia in 1915 reflected the confluence of national interests, international town planning expertise, and local reform agendas.